2021
DOI: 10.1016/j.jep.2021.114488
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism deconvolution of Qing Fei Pai Du decoction for treatment of Coronavirus Disease 2019 (COVID-19) by label-free integrative pharmacology assays

Abstract: Ethnopharmacological relevance Traditional Chinese medicine (TCM) has a long history in the prevention and treatment of pandemics. The TCM formula Lung Cleansing and Detoxifying Decoction (LCDD), also known as Qing Fei Pai Du Decoction, has been demonstrated effective against Coronavirus Disease 2019 (COVID-19). Aim of the study This work aimed to elucidate the active ingredients, targets and pathway mechanism of LCDD related to suppression of inflammatory, immunity reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Other drugs being studied for use in ME/CFS or Long COVID include metformin [ 735–737 ], fenofibrate (which is somewhat protective against reperfusion injury [ 738 , 739 ]), and low-dose naltrexone [ 740–742 ]. While we are no experts, and the mechanisms are normally not well understood [ 743 ], but as a segue to the following section on nutraceuticals, we also note the effective use of certain traditional Chinese and other traditional medicines in acute COVID-19 [ 744–749 ] and their potential for use in Long COVID [ 748–750 ]. This seems like an area well worth further study by those qualified to do so.…”
Section: Anticoagulants Platelet Inhibitors and The Triple Treatmentmentioning
confidence: 99%
“…Other drugs being studied for use in ME/CFS or Long COVID include metformin [ 735–737 ], fenofibrate (which is somewhat protective against reperfusion injury [ 738 , 739 ]), and low-dose naltrexone [ 740–742 ]. While we are no experts, and the mechanisms are normally not well understood [ 743 ], but as a segue to the following section on nutraceuticals, we also note the effective use of certain traditional Chinese and other traditional medicines in acute COVID-19 [ 744–749 ] and their potential for use in Long COVID [ 748–750 ]. This seems like an area well worth further study by those qualified to do so.…”
Section: Anticoagulants Platelet Inhibitors and The Triple Treatmentmentioning
confidence: 99%
“…Take some formulas, which have been included in this meta-analysis, Lian Hua Qing Wen has been proved with regulating angiotensin converting enzyme 2 (ACE2) expression-disorder-caused symptoms and relieve the cytokine storm ( Zheng et al, 2020 ). Some study revealed that acacetin, wogonin, and isorhamnetin were the main active ingredients in Qing Fei Pai Du decoction, ( Li et al, 2022 ); while the target network model noted that some compounds such as licochalcone B acted on multiple targets, and multiple components interacted with the same target such as GPR35, reflecting the synergistic mechanism of Chinese medicine ( Xu F. et al, 2021 ). Another special agent which not included in this trial is a potential mucosal topical agent “Ankaferd hemostat (ABS)”, which was approved with effect of antagonizing proteinase-activated receptors (PARs), mainly PAR-1.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, molecular docking and molecular dynamics can be used to more deeply and objectively study the mechanism of action of small molecules in XFBD that coordinate and interact with each other to treat COVID-19. Some studies have used network pharmacology methods to enrich the targets and pathways of traditional Chinese medicines (such as: Lung Cleansing and Detoxifying Decoction (LCDD)) and explore their therapeutic effects on COVID-19 ( Xu et al., 2021 ). This study not only analyzed and drawed on relevant network pharmacology research results, but also used the supercomputer platform to simulate the relationship between small molecule drugs and protein targets through molecular dynamics.…”
Section: Discussionmentioning
confidence: 99%